Quercetin Inhibits ROS-p53-Bax-caspase-3 Axis of Apoptosis and Augments Gonadotropin and Testicular Hormones in Chronic Unpredictable Stress-Induced Testis Injury - Bin-Jaliah,Ismaeel (Sociedad Chilena de Anatomía, 2021)
SUMMARY: A large body of evidence supports the protective role of the flavonol antioxidant compound quercetin in mammals. We tested the hypothesis that quercetin can protect against the hypothalamus-pituitary-gonadal (HPG) axis defect like a reduction in gonadotropins and testicular hormones and abnormal semen analysis induced by chronic unpredictable stress (CUS), possibly via the downregulation of oxidative stress (ROS) and p53-Bax-caspase-3 pathways. Rats were either exposed to a variety of unpredictable stressors daily before being sacrificed after 3 weeks (model group) or were treated with quercetin (50 mg/kg body weight/day) at the same time the CUS were induced (treated group). Harvested testicular tissues were stained with basic histological staining, and testis homogenates were assayed for the tumor suppressor p53, apoptosis regulator Bax, B-cell lymphoma 2 (Bcl-2), caspase-3, malondialdehyde (MDA), glutathione peroxidase (GPx), and superoxide dismutase (SOD). In addition, harvested epididymis tissues were used to assess semen analysis, and blood samples were assayed for the testicular hormone testosterone, the adrenal cortex hormone corticosterone, and the anterior pituitary gonadotropins, follicular stimulating hormone (FSH) and luteinizing hormone (LH). CUS induced profound testicular damage and significantly (p<0.05) induced p53, Bax, caspase-3, MDA, and corticosterone, which were significantly (p<0.05) inhibited by quercetin except corticosterone. Whereas, quercetin significantly (p<0.05) increased FSH, LH, testosterone, Bcl-2, GPx, and SOD levels that were inhibited by CUS. In addition, CUS induced oligozoospermia, asthenozoospermia, and teratozoospermia, which were significantly (p<0.05) protected by quercetin. Thus, Quercetin protects against CUS-induced HPG defects in rats, which is associated with the inhibition of ROS-p53-Bax-caspase-3 axis.